Bilateral political relations and the security of China's energy imports - Wenguang Tang; Jiacheng Wang; Xiaohui Yuan; Siqi Wang; Qihui Shao; Jian Hu (Energy Exploration & Exploitation, 2024)
As human demand for energy continues to grow, energy security has become an important research topic for national economic and social development. As the country with the highest energy demand and import in the world, China needs to ensure its energy import security in a personal way. Against this research background, this paper investigates the causal relationship between bilateral political relations and China's energy import security. This research selected HS 6-digit percentile trade data from 47 energy-exporting countries engaged in energy trade with China from 2000 to 2020. A trade gravity model was constructed to examine the impact of bilateral political relations on China's energy import security. Multiple empirical analyses were conducted using the PPMLHDFE method to investigate various aspects of the relationship. The research shows that: (1) Bilateral political relations can significantly affect China's energy trade imports. (2) The regional security situation of exporting countries and the signing of free trade agreements with China play a moderating role between bilateral political relations and energy imports. (3) In the heterogeneity analysis, the influence of bilateral political relations on China's energy trade has obvious stage characteristics, and the influence of bilateral political relations on China's energy trade is stronger in countries and regions along the Belt and Road Initiative, and there is a certain path-dependent type of China's energy imports.